Para-aramid fiber as well as preparation method and application thereof

By dissolving COFs and PPTA in concentrated sulfuric acid to prepare paraaramid fibers, the problem that existing PPTA materials cannot meet the modulus requirements in ultra-high-end applications has been solved, and the significant improvement in strength and modulus and the expansion of application fields has been achieved. .

CN119433748AActive Publication Date: 2025-02-14DONGHUA UNIV +1

Patent Information

Application Number
CN202411578192.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-14
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

Existing PPTA materials cannot meet the requirements for material modulus in ultra-high-end applications, especially in deep-sea exploration, mooring, aerospace and other fields.

Method used

The spinning slurry is formed by dissolving covalent organic frame materials (COFs) with polyterephthalyl terephthalyl terephthalyl terephthalyl diamine (PPTA) in concentrated sulfuric acid, and is prepared by filtration, defoaming, spinning and purification operations. Position aramid fiber.

Benefits of technology

It significantly improves the strength and modulus of para-aramid fibers, can meet the requirements of material modulus in ultra-high-end applications, and expands its application areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433748A_ABST
    Figure CN119433748A_ABST
Patent Text Reader

Abstract

The invention discloses a para-aramid (PPTA) fiber as well as a preparation method and application thereof, belongs to the technical field of high polymer materials, and solves the problem that a PPTA material in the prior art cannot meet the requirement of an ultrahigh-end application field on material modulus. The invention discloses a preparation method of para-aramid fiber, which comprises the following steps: uniformly dispersing a covalent organic framework material in concentrated sulfuric acid at room temperature to obtain a sulfuric acid solution of the covalent organic framework material; dissolving poly (p-phenylene terephthalamide) in a sulfuric acid solution of a covalent organic framework material to obtain spinning slurry; filtering, defoaming and spinning the spinning slurry in sequence; and carrying out purification operation to obtain the para-aramid fiber. According to the preparation method provided by the invention, the condensed state of a PPTA molecular chain is regulated and controlled by adding the COFs structural material, and intermolecular microdefects of the PPTA molecular chain are reduced, so that the strength and modulus of the para-aramid fiber are improved, and the application field of the para-aramid fiber is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically to a para-aramid fiber and a preparation method and application thereof. Background Art

[0002] Poly(p-phenylene terephthalamide) (PPTA) has excellent properties such as ultra-high strength, high modulus, high temperature resistance, acid and alkali resistance, and light weight. Its strength is 5 to 6 times that of steel wire, its modulus is 2 to 3 times that of steel wire or glass fiber, its toughness is 2 times that of steel wire, and its weight is only about 1 / 5 of that of steel wire. It does not decompose or melt at a temperature of 560°C. Thanks to the ultra-high strength, modulus, and excellent acid and alkali resistance and high temperature resistance of aramid fiber, it is widely used in military industry, aerospace, lightweight optical cable, automobile weight reduction and other fields, and has an irreplaceable position.

[0003] Due to some micro defects in the molecular chain of PPTA itself, its strength and modulus are relatively limited. At present, the strength and modulus of ordinary para-aramid are 19.5cN / dtex and 85GPa respectively, and the strength and modulus of high-strength and high-model para-aramid can reach 23.5cN / dtex and 110GPa respectively. However, it still cannot meet the requirements of ultra-high-end application fields such as deep-sea exploration, mooring, aerospace and other fields for material modulus (its modulus is required to reach more than 120GPa). Summary of the invention

[0004] The present invention provides a para-aramid fiber and a preparation method and application thereof, which are used to solve the problem that PPTA materials in the prior art cannot meet the requirements of ultra-high-end application fields on material modulus.

[0005] In a first aspect, the present invention provides a method for preparing para-aramid fiber, comprising the following steps: uniformly dispersing a covalent organic framework material in concentrated sulfuric acid at room temperature to obtain a sulfuric acid solution of the covalent organic framework material; dissolving poly(p-phenylene terephthalamide) in the sulfuric acid solution of the covalent organic framework material to obtain a spinning slurry; filtering, degassing and spinning the spinning slurry in sequence to obtain nascent fibers; and purifying the nascent fibers to obtain the para-aramid fiber.

[0006] As a possible implementation manner, the covalent organic framework material structure contains NH bonds, O and benzene rings; and / or the covalent organic framework material structure is a porous two-dimensional structure.

[0007] As a possible implementation, the covalent organic framework material is any one of NKCOF-12, COF-3, NKCOF-45 and NKCOF-41; and / or, the uniform dispersion in concentrated sulfuric acid comprises the following steps: adding the covalent organic framework material to concentrated sulfuric acid at room temperature, stirring at a rate of 20 to 180 rpm; ultrasonically treating at a power of 40 to 200 KHz for 30 to 180 min to obtain a sulfuric acid solution of the covalent organic framework material; and / or, the spinning is performed by dry-jet wet spinning, with a spinneret diameter of 0.05 to 0.2 mm, a number of holes of 150 to 1000, and a fiber linear density of 800D to 1500D; and / or, the purification operation comprises the following steps: alkali washing, water washing, drying and heat treatment of the spun fiber in sequence to obtain the para-aramid fiber.

[0008] As a possible implementation method, the mass ratio of the covalent organic framework material to the poly(p-phenylene terephthalamide) is 0.1-8:1000; and / or the viscosity of the poly(p-phenylene terephthalamide) is 5.5-7.5 dL / g, and the solid content is 18%-20%; and / or the poly(p-phenylene terephthalamide) participates in the reaction in the form of a solution, and its concentration is 19.5wt%; and / or the concentration of the concentrated sulfuric acid is 100%.

[0009] As a possible implementation manner, the poly(p-phenylene terephthalamide) is dissolved in the sulfuric acid solution of the covalent organic framework material at a dissolution temperature of 30 to 90° C. and a dissolution time of 35 to 60 minutes.

[0010] In a second aspect, the present invention provides a para-aramid fiber prepared by the preparation method described in any possible implementation of the first aspect.

[0011] In a third aspect, the present invention provides an application of the para-aramid fiber prepared by the preparation method described in any possible implementation of the first aspect or the para-aramid fiber described in the second aspect in an ultra-high-end field, wherein the ultra-high-end field is a field where the performance requirement for the para-aramid fiber is a modulus ≥ 120 GPa.

[0012] As a possible implementation method, the ultra-high-end field includes deep-sea exploration, mooring, aviation or aerospace.

[0013] As a possible implementation, the para-aramid fiber is used to prepare 24 mm mooring ropes.

[0014] The present invention provides a method for preparing para-aramid fiber, which regulates the condensed state of PPTA molecular chains by adding COFs structural materials, reduces micro defects between molecules, thereby improving the strength and modulus of para-aramid and expanding its application field. COFs is a two-dimensional or three-dimensional network structure formed by lightweight organic molecular units connected by covalent bonds, and thus has the advantages of excellent structural tailorability and functional adjustability, as well as low skeleton density, high porosity, open pore structure, etc. More than 85% of the amide bonds (-CONH-) in the PPTA molecular chain are directly connected to the benzene ring, so it can form a π-π conjugated effect with the benzene ring, and there is a strong interaction force between the molecular chains; at the same time, the macromolecules are arranged in parallel, the free space volume is small, and there is a strong hydrogen bond between the PPTA molecular chains.

[0015] COFs with NH bonds, O and benzene ring structures in their structures can form a large π-π conjugation effect with PPTA molecular chains, enhance the interaction between molecular chains, have high internal rotation potential, and present a parallel rigid straight chain conformation, making the resulting fiber crystals relatively complete and with higher crystallinity; at the same time, NH bonds and O can form more hydrogen bonds with PPTA molecular chains, thereby increasing rigidity and enhancing fiber modulus. COFs materials with porous three-dimensional structures can use their scaffold structure to make COFs act as clamps, effectively embedding a large number of PPTA molecular chains into the surface control, thereby enhancing the lateral interaction between PPTA molecular chains and improving fiber strength and modulus. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 This is the structural formula of the covalent organic framework material NKCOF-12 provided in an embodiment of the present invention.

[0018] Figure 2 The structural formula of the covalent organic framework material COF-3 provided in an embodiment of the present invention.

[0019] Figure 3 This is the structural formula of the covalent organic framework material NKCOF-45 provided in an embodiment of the present invention.

[0020] Figure 4 This is the structural formula of the covalent organic framework material NKCOF-41 provided in an embodiment of the present invention.

[0021] Figure 5 This is a SEM image of the para-aramid fiber A provided in an embodiment of the present invention.

[0022] Figure 6 This is a SEM image of the para-aramid fiber E provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] In order to solve the problem that PPTA materials in the prior art cannot meet the requirements of material modulus in ultra-high-end application fields, an embodiment of the present invention provides a preparation experiment of para-aramid fiber, successfully prepared para-aramid fibers A to para-aramid fibers D, and prepared para-aramid fiber E as a comparison.

[0025] Furthermore, the embodiments of the present invention characterize various properties of para-aramid fibers A to para-aramid fibers E. It can be seen that the para-aramid fibers A to para-aramid fibers D prepared by the present invention have significantly improved linear density, strength and modulus. On the basis of ensuring superior linear density and strength performance, they can also meet the requirements of ultra-high-end application fields for material modulus performance.

[0026] Furthermore, the embodiments of the present invention conduct a test experiment on the application effect of para-aramid fibers A to para-aramid fibers E. It can be known that the para-aramid fibers A to para-aramid fibers D prepared by the present invention all have relatively significant and superior application effects and can meet the application requirements of ultra-high-end fields.

[0027] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0028] Example 1

[0029] This embodiment provides a preparation experiment of para-aramid fiber.

[0030] 10g NKCOF-12 (structural formula: Figure 1The invention discloses a method for preparing a slurry of NKCOF-12 fiber. The slurry is dispersed in 412 kg of concentrated sulfuric acid at room temperature, and ultrasonically stirred at an ultrasonic power of 60 KHz and a speed of 60 rpm for 40 min to obtain a sulfuric acid solution A of NKCOF-12; 100 kg of PPTA is dissolved in the sulfuric acid solution A of NKCOF-12 to obtain a spinning slurry A; the spinning slurry A is filtered and degassed with an accuracy of 20 μm, and then spun by a dry-jet wet spinning method, wherein the spinneret hole specifications used for spinning are 0.05 mm in diameter and 1000 holes; a coagulation bath (coagulation bath concentration is 0.5% sulfuric acid) is passed to obtain a nascent fiber A; the nascent fiber A is alkali washed, washed with water, dried, and heat treated to obtain a para-aramid fiber A.

[0031] 100g NKCOF-41 (structural formula: Figure 4 The invention discloses a method for preparing a slurry of NKCOF-41 fiber. The slurry is dispersed in 412 kg of concentrated sulfuric acid at room temperature, and stirred at an ultrasonic power of 80 KHz and a speed of 120 rpm for 50 min to obtain a sulfuric acid solution B of NKCOF-41; 100 kg of PPTA is dissolved in the sulfuric acid solution B of NKCOF-41 to obtain a spinning slurry B; the spinning slurry B is filtered and degassed with an accuracy of 20 μm, and then spun by a dry-jet wet spinning method, wherein the spinneret hole specifications used for spinning are 0.05 mm in diameter and 1000 holes; a coagulation bath (coagulation bath concentration is 0.5% sulfuric acid) is passed to obtain a nascent fiber B; the nascent fiber B is subjected to alkali washing, water washing, drying, and heat treatment to obtain a para-aramid fiber B.

[0032] 300g COF-3 (structural formula: Figure 2 The method comprises the following steps: dispersing 100 kg PPTA in 412 kg concentrated sulfuric acid at room temperature, stirring at an ultrasonic power of 80 kHz and a speed of 150 rpm for 60 min to obtain a sulfuric acid solution C of COF-3; dissolving 100 kg PPTA in the sulfuric acid solution C of COF-3 to obtain a spinning slurry C; filtering and degassing the spinning slurry C with an accuracy of 20 μm, and spinning the slurry C by a dry-jet wet spinning method, wherein the spinneret hole specifications used for spinning are 0.05 mm in diameter and 1000 holes; passing through a coagulation bath (the coagulation bath concentration is 0.5% sulfuric acid) to obtain a nascent fiber C; alkali washing, water washing, drying, and heat treatment are performed on the nascent fiber C to obtain a para-aramid fiber C.

[0033] 5g COF-3 was dispersed in 412kg concentrated sulfuric acid at room temperature, and stirred at an ultrasonic power of 80KHz and a speed of 150rpm for 60min to obtain a sulfuric acid solution C1 of COF-3; 100kg PPTA was dissolved in the sulfuric acid solution C1 of COF-3 to obtain a spinning slurry C1; the spinning slurry C was filtered and degassed with an accuracy of 20μm, and then spun by a dry-jet wet spinning method, wherein the spinneret hole specifications used for spinning were 0.05mm in diameter and 1000 holes; a coagulation bath (coagulation bath concentration was 0.5% sulfuric acid) was used to obtain a primary fiber C1; the primary fiber C was alkali washed, water washed, dried, and heat treated to obtain a para-aramid fiber C1.

[0034] 800g NKCOF-45 (structural formula: Figure 3 The invention discloses a method for preparing a slurry of NKCOF-45 fiber. The slurry is dispersed in 412 kg of concentrated sulfuric acid at room temperature, stirred at an ultrasonic power of 80 KHz and a speed of 150 rpm for 80 min, and then stirred for 80 min to obtain a sulfuric acid solution D of NKCOF-45; 100 kg of PPTA is dissolved in the sulfuric acid solution D of NKCOF-45 to obtain a spinning slurry D; the spinning slurry D is filtered and degassed with an accuracy of 20 μm, and then spun by a dry-jet wet spinning method, wherein the spinneret hole specifications used for spinning are 0.05 mm in diameter and 1000 holes; a coagulation bath (coagulation bath concentration is 0.5% sulfuric acid) is passed to obtain a nascent fiber D; the nascent fiber D is alkali washed, washed with water, dried, and heat treated to obtain a para-aramid fiber D.

[0035] 100 kg of PPTA was dissolved in 412 kg of concentrated sulfuric acid to obtain a spinning slurry E; the spinning slurry E was filtered and degassed with an accuracy of 20 μm, and then spun by a dry-jet wet spinning method, wherein the spinneret hole specifications used for spinning were 0.05 mm in diameter and 1000 holes; primary fibers E were obtained by a coagulation bath (the coagulation bath concentration was 0.5% sulfuric acid); the primary fibers E were alkali washed, water washed, dried, and heat treated to obtain para-aramid fibers E.

[0036] Example 2

[0037] This embodiment provides a performance characterization experiment of para-aramid fiber.

[0038] The para-aramid fiber A and para-aramid fiber E prepared in the example were subjected to SEM analysis, and the following results were obtained: Figure 5 and Figure 6 The SEM image shown in FIG. 4 shows that the para-aramid fiber was successfully prepared.

[0039] The linear density, strength, modulus and elongation at break of the para-aramid fibers A to E prepared in Example 1 were tested, and the results shown in Table 1 were obtained.

[0040] Table 1 Performance characterization results of para-aramid fiber

[0041]

[0042] It can be seen from Table 1 that, compared with the para-aramid fiber E, the para-aramid fibers A to para-aramid fibers D prepared by the present invention all significantly improve linear density, strength and modulus. On the basis of ensuring superior linear density and strength performance, they can also meet the requirements of ultra-high-end application fields for material modulus performance.

[0043] Example 3

[0044] This embodiment provides an application effect verification experiment of para-aramid fiber.

[0045] The fiber to be tested was used to prepare a 24 mm mooring rope, using 3900000 dtex twisted high model fiber. In this example, the para-aramid fiber C and the para-aramid fiber E prepared in Example 1 were used as the fibers to be tested, respectively, to prepare ropes C and E, and other preparation conditions were the same.

[0046] The results show that the modulus of rope C is 11% higher than that of rope E, and the 0.5% breaking strength elongation (FASE-0.5) is 9% lower; it can be seen that para-aramid fiber C has more excellent application performance.

[0047] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0048] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing para-aramid fiber, characterized in that: The following steps are involved: The covalent organic framework material is uniformly dispersed in concentrated sulfuric acid at room temperature to obtain a sulfuric acid solution of the covalent organic framework material; dissolving poly(p-phenylene terephthalamide) in a sulfuric acid solution of the covalent organic framework material to obtain a spinning slurry; The spinning slurry is filtered, degassed and spun in sequence to obtain primary fibers; The spun fibers are purified to obtain the para-aramid fibers.

2. The preparation method according to claim 1, characterized in that: The covalent organic framework material structure contains NH bonds, O and benzene rings; And / or, the structure of the covalent organic framework material is a porous two-dimensional structure.

3. The preparation method according to claim 1, characterized in that: The covalent organic framework material is any one of NKCOF-12, COF-3, NKCOF-45 and NKCOF-41; And / or, the uniform dispersion in concentrated sulfuric acid comprises the following steps: adding the covalent organic framework material to concentrated sulfuric acid at room temperature, stirring at a rate of 20 to 180 rpm; ultrasonicating at a power of 40 to 200 KHz for 30 to 180 min to obtain a sulfuric acid solution of the covalent organic framework material; And / or, the spinning is carried out by dry-jet wet spinning, wherein the spinneret hole diameter is 0.05-0.2 mm, the number of holes is 150-1000, and the fiber linear density is 800D-1500D; And / or, the purification operation includes the following steps: sequentially performing alkali washing, water washing, drying and heat treatment operations on the spun fibers to obtain the para-aramid fibers.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the covalent organic framework material to the poly(p-phenylene terephthalamide) is 0.1 to 8:1000; And / or, the viscosity of the poly(p-phenylene terephthalamide) is 5.5 to 7.5 dL / g, and the solid content is 18% to 20%; And / or, the poly(p-phenylene terephthalamide) is reacted in the form of a solution with a concentration of 19.5 wt %; And / or, the concentration of concentrated sulfuric acid is 100%.

5. The preparation method according to claim 1, characterized in that: The poly(p-phenylene terephthalamide) is dissolved in the sulfuric acid solution of the covalent organic framework material at a dissolution temperature of 30 to 90° C. and a dissolution time of 35 to 60 minutes.

6. A para-aramid fiber prepared by the preparation method according to any one of claims 1 to 5.

7. Application of the para-aramid fiber prepared by the preparation method according to any one of claims 1 to 5 or the para-aramid fiber according to claim 6 in ultra-high-end fields, characterized in that: The ultra-high-end field is a field in which the performance requirement for the para-aramid fiber is a modulus ≥ 120 GPa.

8. The use according to claim 7, characterized in that: The ultra-high-end fields include deep-sea exploration, mooring, aviation or aerospace.

9. The use according to claim 7, characterized in that: The para-aramid fiber is used for preparing 24 mm mooring ropes.

Citation Information

Patent Citations

  • Preparation method of fiber containing porous covalent organic framework compound

    CN103741243A

  • Covalent bond organic framework nanofiber as well as preparation method and application thereof

    CN114214751A

  • Efficient antibacterial meta-aramid fiber and preparation method thereof

    CN117888224A

  • Membrane material as well as preparation method and application thereof

    CN118027424A

  • Porous covalent organic framework nanofiber membrane and preparation method thereof

    CN118497980A

Cited By

  • Covalent organic framework and polyamide 6 composite fiber and preparation method thereof

    CN119913632A

  • A covalent organic framework and polyamide 6 composite fiber and its preparation method

    CN119913632B